2010
DOI: 10.1111/j.1600-0765.2010.01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of adhesion molecule inin vitroplaque-like formation of macrophages stimulated withAggregatibacter actinomycetemcomitanslipopolysaccharide

Abstract: These findings indicate that ICAM-1 plays an important role in plaque-like formation of LPS-stimulated macrophages. Our microchannel chip is a suitable tool for the investigation of etiological factors of atherosclerosis, including periodontitis, in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…In the present study, the LPS treatment significantly increased the ICAM-1 expression in the RAW264.7 cells while it did not affect L-selectin expression. These results are consistent with the previous report that LPS upregulates the expression of ICAM-1 in RAW264.7 cells, but not that of L-selectin (Takeshi et al 2010). Our results showed that the AF from Rubus fruits and their individual anthocyanins (C3G and C3R) significantly downregulated ICAM-1 expression in the LPS-stimulated RAW264.7 cells.…”
Section: Effects Of the Anthocyanins On Expressions Of Adhesion Molecsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the LPS treatment significantly increased the ICAM-1 expression in the RAW264.7 cells while it did not affect L-selectin expression. These results are consistent with the previous report that LPS upregulates the expression of ICAM-1 in RAW264.7 cells, but not that of L-selectin (Takeshi et al 2010). Our results showed that the AF from Rubus fruits and their individual anthocyanins (C3G and C3R) significantly downregulated ICAM-1 expression in the LPS-stimulated RAW264.7 cells.…”
Section: Effects Of the Anthocyanins On Expressions Of Adhesion Molecsupporting
confidence: 93%
“…These results are consistent with the previous report that LPS upregulates the expression of ICAM‐1 in RAW264.7 cells, but not that of L‐selectin (Takeshi et al . ). Our results showed that the AF from Rubus fruits and their individual anthocyanins (C3G and C3R) significantly downregulated ICAM‐1 expression in the LPS‐stimulated RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 97%
“…In addition to genetic and acquired risk factors that can modify host responses, susceptibility to periodontal disease, as well as its severity and progression, is influenced by environmental factors (3)(4)(5). Aggregatibacter actinomycetemcomitans expresses components that may mediate adherence to mucosal surfaces, enable penetration into epithelial cells, inhibit host defense mechanisms, and elicit gingival tissue destruction and alveolar bone resorption (6,7). A. actinomycetemcomitans is clearly associated with the pathogenesis of aggressive periodontitis (AgP).…”
mentioning
confidence: 99%
“…Furthermore, former studies examined the detection of signals from inflamed endothelial cells. However, it was reported that the expression of ICAM-1 in LPS stimulated macrophages involves the induction of a plaque-like formation, which later leads to cell aggregation [ 24 ]. The increase of ICAM-1 expression also promotes the interaction of macrophages with the endothelium, which eventually leads to inflammation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%